La interpretación sobre el juez nacional en el Tribunal de Justicia de la Comunidad Andina - Mendoza, Yolanda (2019)
Although the preliminary interpretation is considered as a non-contentious community process, its effects make it the main instrument used by the Andean Court of Justice with the purpose of guarantee respect for the Andean Community Law. To comply with such important work, the Community court needs the cooperation of national judges, since they are the only ones authorized to request the preliminary interpretation and to adopt, in their final decisions, the interpretation that this Court of Justice makes on the Andean community standards. In view of that, it is imperative to have an appropriate interpretation of the term national judge, the same one that is described in Article 33° of the Treaty of Creation of the Andean Court of Justice. Such interpretation would ensure the full identification of the legitimate national operator, also considered as a Community judge for their collaboration in the application and in the uniform interpretation of the Andean legal system in the territory of the Andean Community’s Member Countries. After analyzing the main judgments of the Andean Court of Justice related to the interpretation of the term national judge, we verify that this Community body, expressly, does not use the rules of interpretation established in the Vienna Convention on the Law of Treaties of 1969. This Court of Justice opts for an interpretation that extends its meaning and, consequently, understands that the national judge is also an administrative functionary with a jurisdictional function and an arbitrator.